ASSESSING IN-SITU SEMI-NATURAL BUTTERFLY BREEDING APPROACH OF ORNITHOPTERA CROESUS (PAPILIONIDAE) ON BACAN ISLAND, MALUKU UTARA, INDONESIA - Djunijanti Peggie; Duncan Neville; Sih Kahono (BRIN Publishing (Penerbit BRIN), 2021)
Indonesia is rich in endemic species of flora and fauna. One of them is Ornithoptera croesus butterfly, which is endemic to North Maluku. Habitat degradation and trade of this species have caused the populations to decline. To avoid the collection of butterfly specimens from nature and to preserve their habitat and population in nature, a semi-natural butterfly breeding practice at Bacan Island was initiated in 2013. This research was conducted to assess the breeding approach for O. croesus lydius using a qualitative descriptive method. The assessment was based on these variables: the specific ecology of the butterfly; the suitability of the breeding site and development model; the utilization of larval host plants and butterfly nectar plants; and the establishment of the birdwing population at the site. The observations and results are presented here. Based on the assessment, the in-situ semi-natural breeding approach is one of the solutions for sustainable use of this protected species.